Characterization of complete mitochondrial genomes of indigenous Mayans in Mexico - Fuzuki Mizuno; Li Wang; Saburo Sugiyama; Kunihiko Kurosaki; Julio Granados; Celta Gomez-Trejo; Víctor Acuña-Alonzo; Shintaroh Ueda (Taylor & Francis Group, 2017)
Background: The authors have previously published the complete mitochondrial genome (mitogenome) sequences of two indigenous Mesoamerican populations, Mazahua (n = 25) and Zapotec (n = 88). Methods: This study determined the complete mitogenome sequences of nine unrelated individuals from the indigenous Maya population living in Mexico. Results: Their mitogenome sequences could be classified into either of the haplogroups A2 and C1. Surprisingly, there were no mitogenome sequences (haplotypes) that the Maya, Mazahua, and Zapotec people share in common. Conclusions: This indicates that no genetic exchange, at least matrilineally, has occurred among them.